Analysis of pronunciation of Czech phonemes and clusters by Icelandic native speakers - Kopeckova, Michaela (Bohemica Olomucensia, 2019)
The paper discusses methods and outcomes of the analysis dealing with pronunciation of Czech phonemes and phonological clusters by the speakers whose first language is Icelandic. The practical analysis is based on the theoretical background that defines phonetics of Icelandic and the graphemes which Icelandic share with the Czech writing system. The aim of the research is to list potential problems of pronunciation that the Icelandic learners of Czech may face, and to collect the data for the pronunciation exercises aiming specifically at the speakers of the particular language.
Keywords: phonetics; pronunciation exercises; Icelandic language; consonant; vowel; pronunciation